2012
DOI: 10.1002/humu.22107
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of nonsynonymous single nucleotide polymorphisms in human SLC26A9

Abstract: Slc26 anion transporters play crucial roles in transepithelial Cl− absorption and HCO3− secretion; Slc26 protein mutations lead to several diseases. Slc26a9 functions as a Cl− channel and electrogenic Cl−-HCO3− exchanger, and can interact with CFTR. Slc26a9(−/−) mice have reduced gastric acid secretion, yet no human disease is currently associated with SLC26A9 coding mutations. Therefore, we tested the function of non-synonymous, coding, single nucleotide polymorphisms (cSNPs) of SLC26A9. Presently, eight cSNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…SLC26A9 has been recently identified in humans as a Cl − channel present at the apical membrane of lung epithelium [Bertrand et al., ; Demitrack et al., ; Dortwart et al., ; Lohi et al., ; Loriol et al., ]. Controversy exists about Cl − /HCO 3 − exchange activity of SLC26A9 [Chen et al., ; Dorwart et al., ]. In the present study, results obtained from intracellular pH measurements upon Cl − removal (CO 2 /HCO 3 ‐equilibrated solutions) did not support a significant HCO 3 − transport mediated by SLC26A9 (Supplemental Information).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…SLC26A9 has been recently identified in humans as a Cl − channel present at the apical membrane of lung epithelium [Bertrand et al., ; Demitrack et al., ; Dortwart et al., ; Lohi et al., ; Loriol et al., ]. Controversy exists about Cl − /HCO 3 − exchange activity of SLC26A9 [Chen et al., ; Dorwart et al., ]. In the present study, results obtained from intracellular pH measurements upon Cl − removal (CO 2 /HCO 3 ‐equilibrated solutions) did not support a significant HCO 3 − transport mediated by SLC26A9 (Supplemental Information).…”
Section: Discussionmentioning
confidence: 63%
“…p.Arg575Trp was one of the SNPs reported by Chen et al. (). This group did not evidence any functional modification of the Cl − transport by expressing SLC26A9–p.Arg575Trp in X. laevis oocytes contrary to the present data.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These results support a role of SLC26A9 as an alternative chloride channel that may contribute to the regulation of airway surface liquid (ASL) essential for mucus clearance under pathophysiological conditions. Third, data emerging from genetic studies in humans provide independent evidence supporting the role of SLC26A9 as a disease modifier in CF and potentially other chronic obstructive lung diseases [83][84][85][86][87]. Specifically, consistent with a protective function of SLC26A9 in Th2-mediated airway inflammation, it was shown that a functional SNP (rs2282430) is associated with asthma in children [83].…”
Section: Slc26a9mentioning
confidence: 92%
“…Binding of this micro-RNA to the 3′ UTR results in reduced SLC26A9 protein expression, which may result in reduced chloride channel function in vivo. In the meantime, several additional polymorphisms were identified that alter SLC26A9 function by a variety of molecular mechanisms ranging from altered protein expression to decreased or increased chloride channel activity in vitro [84]. Interestingly, some of these variants were recently detected in patients with CF-like lung disease [85].…”
Section: Slc26a9mentioning
confidence: 98%